Motif of Road in Stepan Shevyrev's “Journey to Kirillo Belozersky Monastery” - O. N. Alexandrova-Osokina; Juan Wang (Научный диалог)
This article explores the motif of the road in S. P. Shevyrev's “Journey to the Kirillo-Belozersky Monastery.” It is argued that the road serves as a pivotal narrative and thematic element within the work. Through a detailed analysis, “road narratives” present in the text are identified and classified into two distinct groups: (1) episodes characterized predominantly by their descriptive nature, and (2) episodes where the motif of the road is conceptualized, reflecting the author's geopolitical and historical-philosophical perspectives. This classification supports the assertion that the road motif in the aforementioned work not only mirrors the realities of travel but also encapsulates the writer's historical-philosophical views on Russia's fate, its national historical trajectory, and the character of the Russian people. The relevance of this study is underscored by the growing interest in Shevyrev's oeuvre as a key figure in the literary-historical process of the first half of the 19th century, as well as an enduring fascination with the poetics of documentary-artistic genres. The novelty of this research lies in the relative under-exploration of the work and the chosen analytical perspective, which reveals the expressive means that construct the road motif and traces the mechanisms of its conceptual enrichment.